Pengaruh Model Pembelajaran STEAM terhadap Perkembangan Kognitif Anak Usia 5-6 Tahun - Niken Farida; Rahmi Wardah Ningsih; Anastasia Inta Juwita Ndruru (Departement of Mathematics Education, 2023)
The Influence of the STEAM Learning Model on the Cognitive Development of Children Aged 5-6 Years. As for the purpose of this study is to determine the effect of the STEAM learning model (Science, Technology, Engineering, Arts, Mathematics) on the Cognitive Development of Children Aged 5-6 Years in Umbusohaau Kindergarten. The sample used in this study was 14 children, with the type of research being experimental and the pre-experimental one group pretest and posttest design approach. The technique used in selecting the sample is total sampling. The data obtained from the results of the study were analyzed using SPSS 22 statistics with the mean, median, mode, Shapiro-Wilk normality test, Paired-sample t-test. The results obtained from the study found that the cognitive development of children in the pretest obtained an average of 7.14 with a proportion of 36%. Whereas after the treatment or posttest increased with an average score of 12.71 with a proportion of 64%. And based on the hypothesis test, the results of the paired sample t-test analysis showed the results of t count < t table (value -18.004 < 2.160) and a significant value of 0.02 < 0.05. According to the criteria, if t count < t table, it means that Ho is rejected, Ha is accepted, meaning that there is an influence of the STEAM Learning Model on the Cognitive Development of Children Aged 5-6 Years in Umbusohahau Kindergarten.